Desenvolvimento de interface de operação para sistema autônomo de varredura aérea 3D aplicado à Termelétrica do Pecém/CE - Santos, Judá Teixeira (2021)
Coal-fired power plants required constant control of the amount of coal stored in their stock.This guarantees the supply of the plant and maintains the production of energy. Techniques suchas photogrammetry can solve this problem. However, they have disadvantages compared to lasermapping. The correct control and operation of these systems are essential to properly updatethe plant’s inventory. This work presents the development of a graphical operator interface forthe high-precision three-dimensional aerial mapping system. The developed system has thehardware to rebuild and map the coal yard of UTE Pecém through a point cloud to control theinventory.The aerial system features a LiDAR (Light Detection and Ranging) sensor for acquiring thepoint cloud. It also uses a RTK (Real-Time Kinematic) positioning system to increase thepositioning accuracy of the system, which also influences the reconstruction of the point cloud.This equipment is coupled to an UAV (Unmanned Aerial Vehicle) with an on-board computerfor data processing and communication with the mobile interface.The entire operation of the aerial mapping system is done through a graphical user interface.The interface was developed for mobile devices usingAndroidand written inJava. The mobileinterface presents real-time information from the three-dimensional mapping system. Theinterface has the purpose of facilitating the operation of the UAV and providing informationfrom the aircraft to the operator in the field.At the end of the work, experiments to validate the operation of the system through the interfaceare presented. Experiments to map the coal storage location with the developed system are alsodemonstrated